2008
DOI: 10.1007/s00330-008-1242-0
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic biomechanical assessment of human articular cartilage transplants in the knee using 3-T MRI: an in vivo reproducibility study

Abstract: The aims of this study were to examine the clinical feasibility and reproducibility of kinematic MR imaging with respect to changes in T (2) in the femoral condyle articular cartilage. We used a flexible knee coil, which allows acquisition of data in different positions from 40 degrees flexion to full extension during MR examinations. The reproducibility of T (2) measurements was evaluated for inter-rater and inter-individual variability and determined as a coefficient of variation (CV) for each volunteer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In has been previously demonstrated that focal cartilage lesions, as well as the cartilage repair tissue, are characterized by T 2 elevation [ 14 , 33 35 ]. This focal T 2 increase was attributed either to collagen disorganization or to cartilage swelling, accompanied by water volume increase.…”
Section: Discussionmentioning
confidence: 99%
“…In has been previously demonstrated that focal cartilage lesions, as well as the cartilage repair tissue, are characterized by T 2 elevation [ 14 , 33 35 ]. This focal T 2 increase was attributed either to collagen disorganization or to cartilage swelling, accompanied by water volume increase.…”
Section: Discussionmentioning
confidence: 99%
“…For implanted constructs, non-invasive methods such as MRI [631][632][633][634] and ultrasound [635][636][637] can be applied. Stains such as alcian blue, safranin O (often used together with fast green), and sirius red are regularly employed, along with combinations such as Movat's pentachrome and hematoxylin/eosin to histologically demonstrate the location of glycosaminoglycan, collagen, and other ECM.…”
Section: Assessment and Design Standards For Tissue Engineeringmentioning
confidence: 99%
“…However, none of these studies had more than 2 years of follow-up, a relatively short time to detect degeneration or hypotrophy of the new cartilage. Long-term follow-up and more parameters (81,207) need to be considered in comparative studies.…”
Section: Autologous Chondrocyte Implantation (Aci)mentioning
confidence: 99%